Sustained Release Drug Delivery System with the Role of Natural Polymers: A review - Sharma, Diksha; Dev, Dhruv; Prasad, D.N.; Hans, Mansi (Journal of Drug Delivery and Therapeutics, 2019)
An appropriately designed sustained release dosage form is opted to be a major goal in solving the problems which arises regarding the targeting of a drug to a specific organ or tissue and for controlling its rate of delivery to the target site. The development of oral sustained release system has proven to be a major challenge to formulation scientist due to their inability to restrain as well as localize the system at targeted areas of the gastrointestinal tract. Therefore the development of matrix type drug delivery system is promising option regarding the development of an oral sustained release system. There is availability of wide variety of polymers which helps the formulation scientist to develop sustained/controlled release products. The attractiveness of these dosage forms is increasing because of their awareness towards toxicity and ineffectiveness when administered by oral route in the form of tablets and capsules. Numerous advantages are provided by sustained release products over conventional dosage forms through optimizing various bio-pharmaceutics, pharmacokinetic and pharmacodynamics properties of drugs and finally leads to reduction in dosing frequency to such an extent that only once daily dose is required for therapeutic management with maximum utility of drug with reduction in both local as well as systemic side effects. They can cure or control diseased condition in shortest possible time with smallest quantity of drug to assure greater patient compliance. Polymer swelling, drug dissolution and its diffusion are the known mechanisms for drug release through polymer network.Keywords: Oral drug delivery system, sustained release dosage form, matrix system, polymer swelling, drug diffusion.